2019
DOI: 10.5114/jcb.2019.90466
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of multidisciplinary non-surgical local interventional ablation techniques in primary or secondary liver malignancies

Abstract: Local non-surgical interventional percutaneous ablation represents nowadays an important part of the potential treatment strategies. Although surgical ablation represents the gold standard, in the past decade there was an expansion in the use of non-surgical ablative techniques: radiofrequency, microwave, laser, cryoablation, irreversible electroporation, and interventional radiotherapy (brachytherapy) in primary as well as secondary liver cancers. With the growing experience in the field, there was implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 97 publications
0
31
0
Order By: Relevance
“…Some studies have reported that treatment with TACE and subsequent CT-HDRBT results are associated with a very promising survival rate for patients with unresectable HCC [ 35 ]. From the economic perspective, CT-HDRBT is less expensive than RFA and MWA [ 36 ]. Therefore, the combination of CT-HDRBT with TACE offers a dual advantage in the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that treatment with TACE and subsequent CT-HDRBT results are associated with a very promising survival rate for patients with unresectable HCC [ 35 ]. From the economic perspective, CT-HDRBT is less expensive than RFA and MWA [ 36 ]. Therefore, the combination of CT-HDRBT with TACE offers a dual advantage in the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The dose ranging from 15 to 20 Gy is generally used as a single-fraction HDR brachytherapy to liver, kidney, lung, and breast malignancies [ 10 , 11 , 12 , 13 ]. However, an appropriate single-fraction dose for head and neck cancer in palliative therapy is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, ablative radiotherapy has been revolutionized. BT approach in patients with liver tumors had been modernized and ablative BT was increasingly used as a non-thermal ablation [ 111 , 112 ].…”
Section: The Practice Of Sabt: Outcomes Advances and Perspectivesmentioning
confidence: 99%
“…In patients with liver cancer, BT application allows achieving an excellent local tumor control of up to 96.1% [ 112 ]. Moreover, BT delivered higher survival benefit compared to the best supportive care (median overall survival 23 months vs. 5 months) in those patients [ 112 ].…”
Section: The Practice Of Sabt: Outcomes Advances and Perspectivesmentioning
confidence: 99%